KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DALAM MERENEGOSIASI NORTH AMERICAN FREE TRADE AGREEMENT (NAFTA) MENJADI UNITED STATES-MEXICO-CANADA AGREEMENT (USMCA) PADA MASA KEPEMERINTAHAN DONALD TRUMP - Balqis Febryani; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes America known to many countries in the world as the country with the largest economy in the world. In order to maintain its hegemony, the United States has always participated in an international cooperation. But in 2016, the direction of the foreign policy of the United States underwent a significant change. The rise of Donald Trump as the 45th president of the United States, made the foreign policy direction of the United States turn into a nationalist populist direction. With the goal of